ADAPTATION OF STUDENTS TO THE PROFESSIONAL ACTIVITY OF THE CIVILIAN OPERATIONAL AND RESCUE SERVICE PROTECTION OF THE MOE OF EMERGENCY OF UKRAINE - A.A. Balytska (Academy of Cognitive and Natural Sciences, 2009)
It deals with the adaptive and developing conception of cadets' socialization in course of studying at fire fighting technical higher educational.